(untitled) (Research, Society and Development, 2020)
Groundwater is an excellent alternative to meet public water supply demands, especially in the face of the water crisis and pollution of surface water bodies. Many municipalities throughout the national territory use water from springs for urban water supply. Barra Mansa, a city located in the southern Fluminense region, is an example of this. The aim of this study was to evaluate the water quality of three springs located in the city of Barra Mansa, in order to verify its water potential. The results obtained showed the water potential of the Municipality, revealing, however, the state of degradation and the risk of contamination of groundwater, imposing the need to develop measures to preserve, prevent and mitigate anthropic impacts on the water sources. In this way, the questions proposed here may contribute to a reflection about the exploration of the sources and the implications inherent to its use.